KINETICS AND BALANCE ADSORPSI ION KROMIUM (III) IN SOLUTIONS ON SILICA AND COMPOUND MODIFICATION OF SILICA RESULTS SYNTHESIS FROM GREEN RICE DRINKS - Siti Sulastri; Nuryono Nuryono; Indriana Kartini; Eko Sri Kunarti (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2014)
This study will examine the nature of silica and modified silica in the interaction with Cr (III) ion as an adsorbate. Properties that will be studied are kinetics and equilibrium of Cr (III) adsorption in solution. Studies begins with determining the existence of Cr (III) ion in solution at various pH values, the presence of adsorbent at various pH values, and the adsorption of Cr (III) ion in solution by the adsorbent at various pH values. Based on this data set also can determined some values, e.g the maximum adsorption capacity (notated as Qmax), and the equilibrium constant, the RL value that determined the nature of adsorption were favorable or not favorable. Similarly to the Freundlich isotherm. Adsorption kinetic and equilibrium were performed at pH 5. Each adsorbent has a different kinetic model. All of adsorbents has compatibility with Langmuir 2 isotherm model, and on these condition had favorable adsorption of Cr (III) ion. The highest Qmax value is at HSSN. In the Freundlich isotherm model can be stated that all of the adsorbent is favorable for the adsorption process of Cr (III) ion in solution..